RANCANG ULANG INCINERATOR PORTABEL BARREL DENGAN SENSOR UDARA PEMBAKARAN BERBASIS ARDUINO UNO - Sunaryo; rokhim, Abdul; hakim, Legisnal (SURYA TEKNIKA, 2022)
When conducting a field survey in Terai Bangun Village, Mining District, Regency. Kampar, the results of the interview explained that the amount of waste produced in one week reached 7.2 tons, in one year the waste reached 345.4 tons. The waste generated is 47% organic waste, 45% inorganic waste and 8% hazardous and toxic waste (B3). The purpose of this research is to develop an incinerator, with a household-scale capacity. The efficiency of the combustion rate is expected to be around 500 oC-1000 oC in the combustion chamber. Methods This research performs the work stage in carrying out the design, the design stage aims to obtain designs, patterns, and anarduino uno circuits. In this stage using software, Solidwork 2016, Arduino Uno, and Porteus. design results which include stress, displacement and strain parameters Produce technical drawings that are in accordance with the framework stated in a safe loading condition for the waste burning process.